Analisis Pengaruh Emergency Drill Terhadap Kinerja Kru dalam Situasi Darurat di MV. Wisdom Glory - Adrian Dyca Zandyca; Ari Sriantini; Nyoman Ardiana Listriyawati (CV Insan Kreasi Media, 2026)
Crew performance emergency drill is a structured exercise to test the crew’s readiness and coordination during emergencies (fire, evacuation, medical incidents, hazardous material spills, etc.). It focuses on evaluating response speed, procedural accuracy, radio communication, proper use of PPE, leadership, and accurate headcounts. This study aims to analyze the impact of emergency drills on crew performance in handling emergency situations aboard MV Wisdom Glory. The research is grounded in the Safety of Life at Sea (SOLAS) 1974 Chapter III Regulation 19, which requires all seafarers to regularly participate in emergency training to ensure maritime safety. However, field observations indicate several challenges in implementation, including the vessel’s tight operational schedule and limited training opportunities for newly joined crew members. The research employed a descriptive qualitative method, with data collected through direct observation, questionnaires, and documentation during the researcher’s assignment as Third Officer on MV Wisdom Glory. Data analysis was conducted using the Miles & Huberman model with triangulation to validate the findings. The results reveal that the implementation of emergency drills onboard has met several administrative aspects. Training frequency reached 66.7%, and crew participation was recorded at 77.8%. Nevertheless, only 22.2% of crew members felt the drills realistically reflected actual emergency conditions. Observations further showed delays in donning fireman outfits and launching lifeboats, which may reduce the effectiveness of emergency response. Overall, emergency drills positively influence crew preparedness in emergency situations, yet the quality of execution still requires improvement. Realistic training scenarios, alignment of drill schedules with ship operations, and introductory training for new crew members are recommended. This study is expected to contribute to enhancing maritime safety through more effective, adaptive, and sustainable emergency drills.